Identification of Mepenzolate Derivatives With Long-Acting Bronchodilatory Activity - Tanaka, Ken-Ichiro; Yamakawa, Naoki; Yamashita, Yasunobu; Asano, Teita; Kanda, Yuki; Takafuji, Ayaka; Kawahara, Masahiro; Takenaga, Mitsuko; Fukunishi, Yoshifumi; Mizushima, Tohru (Frontiers in Pharmacology, 2018)
The standard treatment for chronic obstructive pulmonary disease is a combination of anti-inflammatory drugs and bronchodilators. We recently found that mepenzolate bromide (MP), an antagonist for human muscarinic M3 receptor (hM3R), has both anti-inflammatory and short-acting bronchodilatory activities. To obtain MP derivatives with longer-lasting bronchodilatory activity, we synthesized hybrid compounds based on MP and two other muscarinic antagonists with long-acting bronchodilatory activity glycopyrronium bromide (GC) and aclidinium bromide (AD). Of these three synthesized hybrid compounds (MP-GC, GC-MP, MP-AD) and MP, MP-AD showed the highest affinity for hM3R and had the longest lasting bronchodilatory activity, which was equivalent to that of GC and AD. Both MP-GC and MP-AD exhibited an anti-inflammatory effect equivalent to that of MP, whereas, in line with GC and AD, GC-MP did not show this effect. We also confirmed that administration of MP-AD suppressed elastase-induced pulmonary emphysema in a mouse model. These findings provide important information about the structure-activity relationship of MP for both bronchodilatory and anti-inflammatory activities.